Influence of a 3D realistic crack path in the driving forces for fatigue crack growth under mode I+II loading. (August 2020) - Maurel, Vincent; Chiaruttini, Vincent; Abecassis, Manon; Koster, Alain; Dezecot, Sebastien
Highlights: Fatigue crack growth has been investigated in Ti17 and Ti6242 alloys under combined tension and shear. Ti17 crack path and FCGR evolution are continuous thus they are used to test simple assumptions about crack path. Ti6242 crack path is tortuous and yields large oscillations in FCGR. 3D spline interpolation account for complex crack path of Ti6242. Mode mixity and particularly mode III are of importance when considering realistic crack shape. Abstract: The aim of this paper is to test the influence of different crack path models, from oversimplification currently used in literature of a straight crack front orthogonal to the specimen sides to a realistic 3D crack path. On the basis of experimental features observed for Ti17 and Ti6242 alloys under multiaxial loading, a sensitivity analysis is proposed to address the impact of realistic 3D crack path on SIF and FCGR assessment.